2005
DOI: 10.1002/zaac.200570026
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopic Studies on the Surface Chemistry of High‐Surface‐Area Gallia Polymorphs

Abstract: Polymorphs α, β, and γ of Ga 2 O 3 having hexagonal (corundum-type), monoclinic and cubic (spinel-type) structure, respectively, were prepared in a high-surface-area form, and characterized by powder X-ray diffraction. Nitrogen adsorption at 77 K showed these gallia samples to have specific surface areas of 77 (α-Ga 2 O 3 ), 40 (β-Ga 2 O 3 ) and 120 m 2 g Ϫ1 (γ-Ga 2 O 3 ). Fourier transform infrared spectroscopy of adsorbed carbon monoxide (at 77 K) and pyridine (at room temperature) showed that the three gall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…9b), consistent with its still relatively high surface area ( Table 1). It has been reported [30,33,35,53,54], that the diffractogram of -Ga 2 O 3 closely resembles that of γ-and alumina with the exception of a shift towards lower Bragg angles, as expected for the larger Ga 3+ ions. No strong morphological change due to calcination could be detected by SEM or STEM (Fig.…”
Section: 3γ-ga 2 O 3 Formationsupporting
confidence: 57%
See 2 more Smart Citations
“…9b), consistent with its still relatively high surface area ( Table 1). It has been reported [30,33,35,53,54], that the diffractogram of -Ga 2 O 3 closely resembles that of γ-and alumina with the exception of a shift towards lower Bragg angles, as expected for the larger Ga 3+ ions. No strong morphological change due to calcination could be detected by SEM or STEM (Fig.…”
Section: 3γ-ga 2 O 3 Formationsupporting
confidence: 57%
“…Five modifications of Ga 2 O 3 are known: α, β, γ, δ and ε [27] and a thermodynamic description of the system Ga-O has been presented [28]. Among these five modifications, β-Ga 2 O 3 is the most stable modification (mp 1740 °С); it has a monoclinic structure with the oxide ions in distorted ccp arrangement and Ga III in distorted tetrahedral and octahedral sites [29][30][31]. α-Ga 2 O 3 crystallizes in the structure of corundum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] It is reported that the Ga 2 O 3 crystal possesses the following five crystalline forms: a-form, b-form, g-form, d-form and e-form, 20 and among these crystalline forms, b-Ga 2 O 3 crystal, the most stable form (melting point at 1740 1C), has a monoclinic structure equipped with O 2À ions in a distorted ccp arrangement and Ga 3+ ions in distorted tetrahedral and octahedral sites. 21,22 While the a-Ga 2 O 3 crystal could be generated prior to the formation of the b-phase Ga 2 O 3 crystal from the as-prepared precursor, crystallizing in a structure of corundum. 23 Moreover, with a wide bandgap of about 4.7 eV, the b-Ga 2 O 3 crystal has extended transparency to the deep ultraviolet wavelength range among transparent semiconducting oxides, and coupling with a strong absorption below 260 nm.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Among these phases, b-Ga 2 O 3 is the thermodynamically stable one, with monoclinic structure. 20 The a-Ga 2 O 3 phase crystallizes in the structure of corundum, and single crystals can only be grown under specific conditions of temperature and pressure. 21 g-Ga 2 O 3 shows a cubic spinel-type structure, analogous to g-Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%